Elucidating the Role of Tualang Honey as a Growth Supplement for Epithelial Regeneration in an Oral Mucosa Model Fabricated Using Primary Oral Human Cells - Noor Izzati Binti Mokhzani (Universiti Sains Islam Malaysia, 2025)
Matric: 3211391 (FPG)-Restricted until August 2028